An alternative measure of economic inequality in the light of optics - Amlan Majumder (Society for the Study of Economic Inequality, 2014)
An ideal state of development, when viewed with fantasy, is nothing but a state or condition where light touches everybody without refraction. The diagonal line of the Lorenz Curve Framework represents such an ideal condition. In the presence of inequality, however, it deviates or refracts from the ideal condition. In this paper, I try to measure economic inequality from the index of refraction. First, I compute such an index for each stratum to evaluate condition in each and then add all to propose an overall measure of economic inequality, which appears to be a standardised measure of the length of the Lorenz Curve relative to that of the diagonal line. The exercise is done utilising data on distribution of income or consumption from the WDI 2014. Results are lively and remarkable. While an index value of less than 1.00 represents an `anomalous refraction' in Optics, such a condition of inequality is true and too common for many of us (60-80 %) in reality. In contrast to that, in some countries, the index of refraction of the richest group exceeds that of Diamond (2.42), where an index value of 1.00 depicts an ideal condition that is enviable. In regard to technicalities, it goes at par Gini Index and beyond. Additionally, it makes analysis of economic inequality more sensible. Presumably, the proposed index could be a good substitute of the Gini Index as it is found perfectly correlated with the latter by quadratic equation with an Adjusted R Square value of 1.00.
Additional information: A modified version of it appeared as Majumder (2015): http://www.accessecon.com/Pubs/EB/2015/Volume35/EB-15-V35-I2-P110.pdf.
Keywords: D31; D63; 330; Gini index; Inequality; Lorenz curve; Optics; Refractive index; Snell's law; Gini coefficient; Concentration measurement; Lorenz curve; Optics industry